Analisis Bibliometrik: Pola Signifikansi dan Korelasi Penelitian Kepuasan Konsumen - Ela Laela; Septian Cahya Azhari (Jurnal Bisnis dan Kewirausahaan, 2023)
This study identified patterns of significance and correlation in consumer satisfaction research across countries and became the subject of evaluation for future publications. The method used is bibliometric analysis. An analysis was conducted on 2,500 Dimensions.ai indexed publications, with the search keyword "consumer satisfaction" for 2012-2022. The data was processed and analyzed using VOSviewer to map the number of publications, main keywords, authors, affiliations, countries, and citation references. This research produced 182 items and 3 clusters for keywords, 120 items and 61 clusters for authors, 96 items and 8 clusters for affiliations, 43 items and 6 clusters for countries, and 81 items and 75 clusters for citation references. Consumer satisfaction research from 2012-2022 focuses more on factors influencing consumer satisfaction.